Getting ready for the Second World War. Fascist Propaganda and Ideology in L’Avventuroso (1938–40) - Manuela Di Franco (Strenae)
In 1938, the Italian Fascist regime enacted legislation banning foreign comics, specifically targeting the children’s press. As a result, publishers like Nerbini had to radically alter their magazines’ contents to align with the regime’s aim of using the children’s press as a tool for indoctrinating Italian youth with Fascist values. This article takes L’Avventuroso as a case study to investigate how Fascist policies influenced children’s media between 1938 and 1940 – from the ban on foreign comics to Italy’s intervention in World War II – focusing on the transition from American-inspired contents to nationalist propaganda. Through content analysis of Italian-made comics and short novels, combined with socio-historical contextualisation, the article explores the extent to which Fascist rhetoric permeated the children’s press. The analysis examines recurring themes, character archetypes, and iconography to assess the role of comics as a vehicle for propaganda. The study also employs qualitative discourse analysis to trace the alignment of narrative structures with Fascist ideology. By examining nationalistic and propaganda contents in L’Avventuroso, the article provides a nuanced understanding of how Fascist policies at the onset of World War II influenced the publishing of comics, offering insights into the regime’s use of children’s media as a tool for propaganda.